Hervé Guibert: Writing the Spectral Image - Donna Wilkerson (Studies in 20th & 21st Century Literature, 1995)
This paper explores the relationship existing between AIDS (in particular the body-with-AIDS or the corps sidaïque), writing, and the spectral image in Hervé Guibert. While taking into account postmodern theory on the image, photography, and the notion of the "real," this essay examines the similitude between the image as plague and AIDS in order to reveal some central components of Guibert's postmodern conceptualization—namely the complex interplay of fact and fiction as it pertains to the body-with-AIDS. For example, the body is a privileged site from which the text radiates. It can also be mistaken for the "real" body of the narrator, since Guibert himself died of AIDS. Yet because it is a deteriorating body, it depends on fictional images to survive, thus creating a body-of-writing that is the spectral image. Therefore, the body, like writing, relies on the "fake" in order to exist. The spectral image replaces the dead body (the body-with-AIDS) and creates a system of fractal representation. In this manner, it indeed manifests Baudrillard's notion of the hyperreal and the simulacrum. This paper demonstrates how Guibert's writing serves as an interesting example of fiction "contaminated" by the "real" and contributes to our understanding of postmodern representation and AIDS in the contemporary novel.
Keywords: Hervé Guibert; corps sidaïque; AIDS; body-with-body-AIDS; postmodern theory; fact; fiction; body